Effects of four cost-effective amendments on the synchronous stabilization of As, Zn, Cu and Cd in contaminated mixture of residue and soil from an arsenic smelting site. Issue 3 (June 2022) - Zhang, Ge; Yang, Huifen; Jiang, Meiling; Zhang, Qingping
Abstract: The effects of four cost-effective amendments including flue gas desulfurization gypsum (FGDG), red soil (RS), biofuel ash (BA) and limestone (LS) on the synchronous stabilization of As, Zn, Cu, Cd in acid mixture of residue and soil (MRS) from an abandoned As smelting site were investigated in this work. The change of environmental pH, EC, CEC and heavy metal fractions also have been examined. The four amendments stabilized the heavy metals in the order of BA>LS>FGDG≈RS. The correlation analysis indicated that the change of pH dominated the stabilization of heavy metals. And the application of BA and LS could efficiently increase the environmental pH. The treatment of 3% BA and LS immobilized As, Zn, Cu, Cd by 62.03%, 97.86%, 99.81%, 90.39% and 38.49%, 99.96%, 99.99%, 99.62% respectively, following an obvious decreasing of F1+F2 for As and B1 for Zn, Cu. But no significant transformation of speciation distribution appeared for Cd. The stabilization of Zn, Cu, Cd was achieved through their precipitation as carbonate and hydroxide in the high pH, as well as forming Me-bearing silicate (Me=Zn, Cu, Cd) with the amorphous silicate in BA. And As was immobilized by transforming unstable As into the precipitation of Ca-As compounds due to the alkaline circumstance and released Ca 2+ from BA and LS. The results demonstrated that the BA and LS were cost-effective stabilizers for As, Zn, Cu, Cd in acid MRS. Graphical Abstract: ga1 Highlights: ● The feasibility of four low-cost amendments on MRS stabilization were examined. ● The comprehensive stabilization effects of HMs were BA > LS > FGDG≈RS. ● The pH presented high positive correlation with stabilization efficiency of HMs.